ETHICAL DILEMMAS IN THE PUBLIC SECTOR - Silvia PUIU (Management & Marketing)
The article offers an insight on the ethical dilemmas specific to a public sector and brings some suggestions for coping with these. Ethics management is a complex system that deals also with ethical dilemmas. The instruments and tools of ethics management are helpful in dealing with these issues. There are a lot of cases in which public employees do not know what to do or how to react in a certain situation, so, a debate on this subject is very useful for people working in public institutions.